Analisis Pemilihan E-Wallet Bagi Mahasiswa Dengan Penerapan Metode Analytical Hierarchy Process (Studi Kasus: Universitas Pembangunan Nasional Veteran Jakarta) - Alyssa Fathiyah; Ermatita Ermatita; Rudhy Ho Purabaya (JOINS (Journal of Information System), 2024)
Students as the easiest element of society to transition digitally using electronic wallets to pay for daily needs, coupled with the promos provided by electronic wallet companies clearly adds to the appeal of this. Of the many electronic wallets, this study will discuss which electronic wallet is the most ideal choice for students, namely OVO, Gopay, DANA by analyzing the criteria based on interface design, reliability, responsiveness, trust, and privacy and security. This research was conducted using the Analytical Hierarchy Process method and the research respondents were students of the Jakarta Veterans National Development University. Based on the results of the analysis, it is concluded that the criteria with the highest priority are security and privacy with a weight of 0.482877, then trust of 0.229895, responsiveness of 0.133409, reliability of 0.099123, and finally interface design of 0.054696, and it is also concluded that the best alternative electronic wallet used by UPNVJ students are Gopay with the highest priority weight (0.3650819544), followed by DANA with the second highest priority weight (0.3409298301), and ended by OVO with the lowest priority weight (0.2939882129).